THE ROLE OF FED SPEECH SENTIMENT SIGNALS IN SHAPING US MARKET RESPONSE - Arshad, Asma (PEOPLE: International Journal of Social Sciences, 2024)
The Federal Reserve’s communication shapes US investor decisions and market dynamics. This paper examines the impact of the Fed governor speeches’ sentiments signals on the US equity market performance from June 1996 to Sep 2023. The sentiment index is calculated using individual Lexicon dictionaries (AFINN, Bing, NRC, and Loughran McDonald) and their combined PCA scores. Our findings revealed a negative relationship suggesting that a positive (negative) sentiment brings a significant decrease (increase) in the cumulative abnormal return on the event window (+2). These results provide valuable insights into the dynamic nature of the US equity market in response to the Federal Reserve’s communication for regulators, policymakers, and other stakeholders of the equity market.